Low voltage crossing strategy for all-DC power generation system of onshore wind power based on battery energy storage - Xunzhe CAO; Fengting LI; Chunya YIN; Jiangshan LIU (电力工程技术)
The all-DC system of onshore wind power can effectively solve the problems of harmonic resonance and reactive power transmission，which is the development direction of wind power generation system. The all-DC system of onshore wind power has a low-voltage ride-through (LVRT) capability and can guarantee voltage stability. Based on the topology and operation control strategy of the onshore wind power all-DC power generation system，the surplus power gathered in the DC link of the system is analyzed during the grid-side voltage dips and the applicability of conventional LVRT strategies is analyzed in the wind power all-DC system. Considering the grid requirements for wind power system energy storage configuration and the self-starting characteristics of wind turbines，a LVRT control strategy based on battery energy storage is proposed. This strategy can store the surplus power of the DC bus when low voltage faults occur. The all-DC power generation system of onshore wind power is built by PSCAD/EMTDC，and the proposed strategy is verified by simulation. The results show that the proposed control strategy can improve the low-voltage ride-through capability of the all-DC system of onshore wind power，and promote the rapid recovery of DC bus voltage. Battery storage absorbs surplus energy during faults and provides energy during self-start of the wind turbine. This strategy can improve the utilization of energy and storage.